2016
DOI: 10.1080/17515831.2016.1247132
|View full text |Cite
|
Sign up to set email alerts
|

Dry sliding wear properties of unhybrid and hybrid Al alloy based nanocomposites

Abstract: Nanosize B 4 C and/or MoS 2 particles reinforced AA2219 alloy composites were prepared using the stir casting process. The wear properties were evaluated for several speed (3.14-5.65 m s −1 ), load (10-50 N) and distance (0-2500 m) conditions. The nanoparticles dispersion, density, wear resistance, morphology of the worn surface and loose wear debris were discussed in detail. The wear resistance improvement results by nanoparticle addition correspond well with the hardness. Between the nanocomposites, hybrid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Most of the brake material studies on MMCs are Fe, Cu, Ni, Mg or Al-based MMCs with uniform size particle reinforcements. 12,[14][15][16][17][18][19][20][21][22][23][24][25] The factors influencing the wear and friction of MMCs are usually classified into two groups, one is the material and process parameters e.g. size, shape, volume fraction and size distribution of the particles, interface bonding strength, matrix type, type of processing and heat treatment, and other one is the testing conditions e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the brake material studies on MMCs are Fe, Cu, Ni, Mg or Al-based MMCs with uniform size particle reinforcements. 12,[14][15][16][17][18][19][20][21][22][23][24][25] The factors influencing the wear and friction of MMCs are usually classified into two groups, one is the material and process parameters e.g. size, shape, volume fraction and size distribution of the particles, interface bonding strength, matrix type, type of processing and heat treatment, and other one is the testing conditions e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that the traditional method of experiment design necessitates extensive resource consumption, assessing the combined effects of applicable components is difficult. In previous work [20], a thorough explanation of factor selection was provided, and it was concluded that, of the four factors considered, sliding speed has the least effect on wear rate. As a result, the least significant factor was removed from the current work, and because this work focuses on the influence of ageing temperature on wear behavior, it was decided to consider the important factors as load, sliding distance, and ageing temperature.…”
Section: Response Surface Methodologymentioning
confidence: 99%
“…Heat-treated composites have higher hardness when compared to unheated composites. The reason for this could be that a much harder intermetallic phase has formed, and ice quenching improves composite hardness by stabilizing the intermetallic phase [20]. Both quenching conditions resulted in changes in wear resistance.…”
Section: Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Dry condition sliding wear behavior of Al/B 4 C nanocomposites produced by mechanical milling and hot pressing [17], milling and hot extrusion [18,19], friction stir processing [20], stir casting [21] and ultrasonic assisted stir casting [22][23][24] are the few studies reported. Sharifi et al [17] produced Al-B 4 C bulk nanocomposites by ball milling and hot pressing method.…”
Section: Introductionmentioning
confidence: 99%